Ecology of healthcare in an urban and rural area of Gampaha district of Sri Lanka: a community-based prospective study on symptom prevalence and healthcare utilization - S. S. Withana; K. Mendis; U. P. Liyanage; S. Nandasena; A. R. Wickremasinghe (BMC Health Services Research)
Abstract Background The 55 million visits to government outpatient departments (OPD) in Sri Lanka in 2014, is estimated to increase to 100 million in 2027. The private OPD visits in 2014 was estimated at 50 million per annum. In primary care, there is a paucity of medical records, research on symptoms and healthcare seeking behaviour. We aimed to determine the symptom prevalence and healthcare seeking pattern of residents in Gampaha district, Sri Lanka. Methods A community-based prospective study using a participant-held symptom diary and interviews were conducted in two areas, Ragama (urban) and Mirigama (rural), in the Gampaha district of Sri Lanka during May–June 2018. For each area, three midwife areas were randomly chosen. Clusters of 15–20 households were selected from 5–6 random locations from each midwife area. Results 2046 individuals from 557 households participated. Majority were females (n = 1127, 55.1%). There were 1207 (59%) from Mirigama area. Among participants, 1919 (93.8%) reported symptoms. Phlegm (n = 4200, 7.0%), leg pain (n = 3943, 6.6%) and cough (n = 3153, 5.3%) were top symptoms among all symptoms reported; the musculoskeletal group (n = 18,081, 30.4%) predominated. 924 (45.1%) participants sought treatment, 763 out of 2046 participants (37.3%) sought allopathic treatment. Private sector visits were more (n = 515, 25.2%). The decision to seek private or public healthcare services was influenced by income. Persons with higher income preferred a private institution. Of the 46 (2.3%) hospital admissions, 42 (91.3%) were to public hospitals, of which, 19 (41.3%) were to teaching hospitals, and 4 (0.9%) to a private institution. Conclusions The population had a high prevalence of symptom reporting (93.8%) and a high healthcare seeking behaviour (45.2%). Among those who sought allopathic treatment, the majority preferred private ambulatory care. 90% of hospital admissions (42/47) were to public hospitals. Provision of ambulatory care services should be prioritized in further development of the health services.